Ist Natur ein biblisches Wort? Naturtheologie in Geschichte und moderner Zeit – zu den frühen, dialektischen Äusserungen in Emil Brunners Obstaldener Predigten - Fabienne STEINER (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
Natural Theology: Is Nature a Biblical Word? In my article, I would like to show Emil Brunner’s early thoughts and statements that he makes in his sermons in Obstalden. These sermons are still unknown and unpublished. It is mostly claimed that Brunner entered in a modern and dialectical phase because of his colleague in the Reformed Church, Karl Barth. True is that they later had intense discussions about theses and antitheses in their first dialectical phase from 1919 to 1934. Brunner, however, makes new dialectical thoughts about nature much earlier than, and without, Barth – for example, already in 1915, when he describes God’s community as a natural element of life and succeeds with it in a synthesis of nature and word revelation. He can even be considered as a dialectical forerunner because he reflects arguments of modern theology at this early time.